(x-3)+13x=5(7+4x)

Simple and best practice solution for (x-3)+13x=5(7+4x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (x-3)+13x=5(7+4x) equation:


Simplifying
(x + -3) + 13x = 5(7 + 4x)

Reorder the terms:
(-3 + x) + 13x = 5(7 + 4x)

Remove parenthesis around (-3 + x)
-3 + x + 13x = 5(7 + 4x)

Combine like terms: x + 13x = 14x
-3 + 14x = 5(7 + 4x)
-3 + 14x = (7 * 5 + 4x * 5)
-3 + 14x = (35 + 20x)

Solving
-3 + 14x = 35 + 20x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-20x' to each side of the equation.
-3 + 14x + -20x = 35 + 20x + -20x

Combine like terms: 14x + -20x = -6x
-3 + -6x = 35 + 20x + -20x

Combine like terms: 20x + -20x = 0
-3 + -6x = 35 + 0
-3 + -6x = 35

Add '3' to each side of the equation.
-3 + 3 + -6x = 35 + 3

Combine like terms: -3 + 3 = 0
0 + -6x = 35 + 3
-6x = 35 + 3

Combine like terms: 35 + 3 = 38
-6x = 38

Divide each side by '-6'.
x = -6.333333333

Simplifying
x = -6.333333333

See similar equations:

| 2x+2x+24=0 | | x^2+18x+43=0 | | -22+20(p+20)=8-10(4p+22) | | 15/75=p/100 | | 2x-2x-24=0 | | f(x)=fx^2 | | 2/3(d)-2=4 | | 45+49/7*4 | | 2(b+2)-(7+b)=-5 | | 6(0)-8y=-48 | | -4(y+1.1)=3(y+3.9) | | 6x^2-xy-y^2-2x+y=0 | | 5=m/9 | | x=-32y^2 | | (4y+6)-(4+3y)=8 | | x-(-4)=16 | | h+3(h+4)=20 | | (2+i)(-7+5i)= | | 5(-8)+2y=8 | | 2x+2x-24=0 | | 5.7+1.7n=2.13 | | 2(X-3)=5(7-X) | | 12p=6(5p+7) | | (2+i)-(-7+5i)= | | 0=2x-13 | | m-(-2)=6 | | x^3-8x^2+9x+6=0 | | x=yx+2y | | -3(2x+4)+1=-13 | | 3y-5=3-2y | | y+4=-21 | | x-3(x+1)=9 |

Equations solver categories